The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/0363546513482297
|View full text |Cite
|
Sign up to set email alerts
|

Relevant Anatomic Landmarks and Measurements for Biceps Tenodesis

Abstract: The MTJ of the biceps begins further proximal than may be appreciated intraoperatively. Knowledge of the anatomic relationships between the LHBT, its MTJ, and the pectoralis major tendon provides helpful guidelines for the biceps tenodesis site. The final resting spot of the most distal aspect of the MTJ of the LHBT after tenodesis should be approximately 3 cm distal to the inferior edge of the pectoralis major tendon footprint on the humerus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 10 publications
0
21
1
1
Order By: Relevance
“…A recent anatomic study by Lafrance et al 43 described the height of the pectoralis major tendon to be 3.73 AE 0.83 cm in the region of the biceps tendon, where open subpectoral tenodesis is performed. Combining this with the measurements of Murachovsky et al, 44 the average distance from the top of the humerus to the inferior border of the pectoralis major tendon is 8.49 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent anatomic study by Lafrance et al 43 described the height of the pectoralis major tendon to be 3.73 AE 0.83 cm in the region of the biceps tendon, where open subpectoral tenodesis is performed. Combining this with the measurements of Murachovsky et al, 44 the average distance from the top of the humerus to the inferior border of the pectoralis major tendon is 8.49 cm.…”
Section: Discussionmentioning
confidence: 99%
“…9,39 Additionally, there has been increasing recognition that restoration of the anatomic length-tension relationship of the long head biceps is a critical aspect of the tenodesis procedure. 22,42,43 These data are valuable to orthopaedic surgeons using these techniques, because little data exist guiding practitioners regarding the differences in these commonly used methods.…”
mentioning
confidence: 99%
“…Restoration of the anatomic LHBT length-tension relation is a principal consideration when performing BT, particularly if considering cosmesis and secondary function. 7,8 Denard et al 8 suggested that the normal anatomic station can be maintained when the LHBT is reinserted at the proximal articular margin of the bicipital groove with a 25-mm bone socket and minimal tendon resection. However, tenodesis at this site largely precludes assessment of the LHBT musculotendinous junction, which typically begins 2.2 cm distal to the proximal edge of the pectoralis major tendon insertion.…”
Section: See Related Article On Page 23mentioning
confidence: 99%
“…However, tenodesis at this site largely precludes assessment of the LHBT musculotendinous junction, which typically begins 2.2 cm distal to the proximal edge of the pectoralis major tendon insertion. 7 Of concern, Werner et al 9 reported that suprapectoral BT was frequently associated with over-tensioning of the LHBT, resulting in decreased load to failure and a greater incidence of failure by implant pullout compared with subpectoral BT. Conversely, Forsythe et al 6 found no incidence of bicipital complications in either cohort, and statistically significant improvements in functional scores were found in both cohorts without notable differences in any primary or secondary outcome measures.…”
Section: See Related Article On Page 23mentioning
confidence: 99%
“…8,9 Não há um consenso claro sobre o melhor tratamento cirúrgico para lesões do TCLB 10 Além disso, não existe um método consistente para assegurar o restauro da tensão bicipital adequada no período pós-operatório. 11 Nosso objetivo foi determinar a presença de IG no músculo bíceps braquial após o tratamento das lesões do TCLB (tenodese ou tenotomia) e estabelecer uma relação entre essa possível IG e alterações no comprimento da fibra muscular, presença de deformidades e força.…”
Section: Introductionunclassified